The Effect of Some Exercises on Some Aerobic and Anaerobic Physical Capacities and Physiological Variables for AL- Yarmouk University Students - Mohammad Bny Melhim (My University, 2012)
The aim of this study was to investigate the effect of some exercises on some aerobic and anaerobic physical capacities and physiological variables. The sample of the study consisted of (38) students registered at (fitness for all) from AL-Yarmouk University. Aerobic and anaerobic physical abilities measurements were taken, and they were consisted of (10s) push up, (30m) Running, Broad jump, (200m) Running, (30s) Push up, (60s) Sit up, (1609m) Running, And some physiological variables (Heart beats rate, Systolic blood pressure, Diastolic blood pressure, and Respiratory rate), before and after Appling the suggested exercises during (12) weeks, two training units for one week, and one Hour and half time per each training unit. The results indicated that there were statistically significant differences of aerobic and anaerobic physical abilities and physiological variables before and after application exercises, While the results revealed that there was no improvement for running (30m) test.

هدفت الدراسة التعرف إلى أثر بعض التدريبات الرياضية على بعض القدرات البدنية الأوكسجينية واللاأوكسجينية والمتغيرات الفسيولوجية، وتكونت عينة الدراسة من طلاب مساق اللياقة البدنية للجميع في جامعة اليرموك، والبالغ عددهم (38) طالباً، وأخذت اختبارات القدرات البدنية الأوكسجينية واللاأوكسجينية وتمثلت في (ثني ومد الذراعين من الانبطاح المائل خلال (10ث)، وعدو (30م)، والوثب الطويل من الثبات، وعدو (200م)، وثني ومد الذراعين من الانبطاح المائل خلال (30ث)، والجلوس من الرقود خلال (60ث)، وجري (1609م)، وبعض المتغيرات الفسيولوجية (معدل ضربات القلب، وضغط الدم الانقباضي، وضغط الدم الانبساطي، ومعدل التنفس)، وذلك قبل وبعد تطبيق التدريبات المقترحة والتي تكونت من (12) أسبوعاً، وبواقع وحدتين تدريبيتين للأسبوع الواحد، ولمدة ساعة ونصف للوحدة التدريبية الواحدة. وأشارت نتائج الدراسة إلى وجود فروق ذات دلالة إحصائية على القدرات البدنية الأوكسجينية واللاأوكسجينية والمتغيرات الفسيولوجية قبل وبعد تطبيق التدريبات الرياضية، في حين لم تشر النتائج عن وجود تحسن على اختبار عدو (30م).
أثر بعض التدريبات الرياضية على بعض القدرات البدنية الأوكسجينية واللاأوكسجينية والمتغيرات الفسيولوجية لدى طلبة جامعة اليرموك